Characterization and role of gut bacterium Bacillus pumilus on nutrition and defense of leafhopper (Amrasca biguttula biguttula) of cotton - SIVAKUMAR, G; RANGESHWARAN, R; YANDIGERI, M S; MOHAN, M; VENKATESAN, T; BALLAL, CHANDISH R; RAMANUJAM, B; YALASHETTI, SANJAY; KUMARI, SURABHI; VERGHESE, ABRAHAM (The Indian Journal of Agricultural Sciences, 2017)
Five culturable gut bacteria associated with single leafhopper [A. biguttula biguttula (Ishida)] (Hemiptera: Cicadellidae) of Guntur field population were characterized through morphological and 16S rDNA sequences. The characterized gut bacteria were Staphylococcus pasteuri, Enterococcus silesiacus, Bacillus amyloliquefaciens, Enterobacter asburiae and Bacillus pumilus. Among these, Bacillus pumilus was chosen for studying its role on host nutrition and defense. The role of the gut bacterium B. pumilus on insect defense against entomofungal pathogens and nutrition was studied under in vitro condition by dual culture technique and other bioassays. The gut bacterium B. pumilus inhibited the mycelial growth of all four major entomofungal pathogens. Maximum growth inhibition (2.0cm) was recorded on Beauveria bassiana followed by Metarhizium anisopliae (1.7cm), Paecilomyces fumosoroseus (1.6cm) and Lecanicillium lecanii (1.5cm) as compared to control. In vitro experiments proved the production of digestive enzymes such as cellulase, pectinase, amylase and protease from B. pumilus. The present study characterized the gut bacteria associated with A.biguttula biguttula and studied the role of the gut bacterium B.pumilus on host nutrition and defense against entomofungal pathogens for the first time in the world.